KAMU KATILIM BANKACILIĞININ BANKACILIK SEKTÖRÜNE BEKLENEN ETKİLERİ. - YANIK, Ramazan; SUMER, Serpil (Electronic Turkish Studies)
Today, many countries have become competed with each other in order to be central to the Islamic finance sector. Participation banks in our country first started operating under the name of "Private Finance Institutions" in 1983. The names of these institutions in the world, which are changed as the result of the legal regulatıon to name participation banking in 2005 are known as Interest Free Banking and Islamic BankingTurkey, which is in competition with other countries in participation banking, made a positive initiative in this issue and the Ziraat Participation Bank, which is the first participation bank in the public, operated in 2015. It is believed that this initiative will contribute to Turkey's goal of becoming the world's top ten economies for 2023. In 2016, Turkey's second public participation bank, the Vakıf Participation Bank, has opened and started to operate. In this study, the concept of participation banking, the methods of fund collection and fund utilization of participation bank is tried to be explained. Besides, it has aimed to give information about the participation banks operating in Turkey. A survey has been counducted to measure the expected effects of public participation banking on the banking sector in Erzurum, Erzincan, Kars and Ağrı in the Eastern Anatolia Region. With this study, it has been tried to measure the level of perception of the purpose of entry of the public banks included in the participation banking sector in this last two years by the bank employees. Obtained data have analyzed by Kruskal Wallis, Mann-Whitney U test in the SPSS (Statistical Program For Social Sciences) program.